Fabrication, Physicochemical Characterization and Evaluation of In vitro Anticancer Efficacy of a Novel pH Sensitive Polymeric Nanoparticles for Efficient Delivery of Hydrophobic Drug against Colon Cancer - Manikandan Mahalingam, Kannan Krishnamoorthy (Journal of Applied Pharmaceutical Science, 2015)
Objective: The present investigation was aimed to overcome the limitations and to enhance the incorporation of the hydrophobic drug into polymeric nanoparticles and characterize the prepared nanoparticles and also to evaluate the in vitro anticancer efficacy of prepared nanoparticles.Method: Nanoprecipitation method was used to prepare plain and hydrophobic drug (Camptothecin) loaded polymeric nanoparticles. Prepared nanoformulations were evaluated for average particle size, particle size uniformity, surface area, zeta potential, surface morphology, drug content, encapsulation efficiency, drug loading, in vitro release, anticancer activity and stability studies at long term and accelerated storage conditions.Results: Plain and Camptothecin loaded polymeric nanoparticles were successfully prepared by nanoprecipitation method using stirring technique. Prepared Camptothecin encapsulated polymeric nanoparticles were (a) spherical in shape with size < 100 nm, displayed excellent uniformity with 20 mV; (b) showed > 95% release in colonic environment; (c) demonstrated enhanced anticancer activity than pure Camptothecin; and (d) extremely stable at both long term and accelerated storage conditions.Conclusion: In summary, the investigation concluded that the prepared Camptothecin encapsulated polymeric nanoformulations may be considered as an attractive and promising formulation which significantly overcome the limitations of Camptothecin and synergistically enhance its anticancer activity.
Keywords: Camptothecin, nanoprecipitation, anticancer activity, stability studies.